Interlaminar fatigue crack growth behavior of MWCNT/carbon fiber reinforced hybrid composites monitored via newly developed acoustic emission method - G. Romhany; G. Szebenyi (eXPRESS Polymer Letters)
The aim of this research was the investigation of the effect of carbon nanotube addition on the mode I interlaminar fatigue properties of carbon fiber reinforced composites. The authors developed a localization methodology to track the interlaminar fatigue crack front using the acoustic emission (AE) technique. According to the test evaluation the carbon nanotube reinforcement decreased the crack propagation rate by 69% compared to the composite containing no nanotubes. Besides that, the fatigue life also increased significantly, the nanotube reinforced composite could withstand 3.8-times more cycles to failure than the unfilled matrix composite.